2015
DOI: 10.1055/s-0034-1396957
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Embolization of Ethiodized Oil following Intranodal Lymphangiography

Abstract: Intranodal lymphangiography (IL) has supplanted pedal lymphangiography (PL) as an easier and more practical approach to opacifying lymphatic vessels for interventional radiologists treating refractory chyle leaks. As more interventional radiologists-many of who are not trained in or have not performed PL-incorporate IL into their practice, it is imperative that they be familiar with the risks of lymphangiography, including pulmonary and systemic embolization of oily contrast material. Herein, the authors repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…To mitigate this risk, we performed systemic-to-pulmonary venous collateral embolization and temporary fenestration occlusion in these patients. Sheybani et al 29 described cerebral embolization in patients without right-to-left shunt resulting in neurological deficit. The mechanism by which systemic embolization occurred in the 1 patient in this study is not completely understood because the patient already had complete occlusion of the TD and he did not have any known right-to-left shunts.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate this risk, we performed systemic-to-pulmonary venous collateral embolization and temporary fenestration occlusion in these patients. Sheybani et al 29 described cerebral embolization in patients without right-to-left shunt resulting in neurological deficit. The mechanism by which systemic embolization occurred in the 1 patient in this study is not completely understood because the patient already had complete occlusion of the TD and he did not have any known right-to-left shunts.…”
Section: Discussionmentioning
confidence: 99%
“…These 28 articles included 5 large original case series with > 10 patients (Category I data) and 3 small original case series with 3-9 patients (Category II data) [15,[19][20][21][22][23][24][25]. The other 20 articles included were case reports and other short reports such as letters to the editor and technical notes with < 3 patients (Category III data) [14,17,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. None of these articles included a prospective study or a randomized controlled trial.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…for 8/20 articles) [28, 32, 33, 36-40, 42, 43]. In 2 articles, however, significant complications, morbidity and/or mortality are described [29,41]. In the article of Taki et al, acute respiratory distress syndrome was reported as a CL-related major complication after transpedal CL, and the patient developed pulmonary fibrosis necessitating domiciliary oxygen therapy due to permanent hypoxemia [41].…”
Section: Technical Aspects Of CLmentioning
confidence: 99%
See 1 more Smart Citation
“…If conservative management fails, bipedal [13] or intranodal [2] lymphangiography should be attempted. Potential complications related to the intralymphatic injection of ethiodized oil are rare and include paradoxical cerebral embolization and lung emboli [14]. Other treatment options are somatostatin analogues, repeat paracentesis or insertion of a tunneled peritoneal drainage catheter [15].…”
Section: Discussionmentioning
confidence: 99%